Frugal innovation in the expansion of a multinational subsidiary in an emerging market - Maísa Arend; Cláudia Felippe Ramos; Yeda Swirski de Souza (Gestão & Produção, 2023)
Abstract Frugal innovation consists of creating solutions based on the parsimonious use of resources with essential quality, design, and functionality, offered to customers with lower purchasing power. This study aims to analyze how a frugal innovation evolves in a multinational company during its expansion into a new market at the base of the pyramid (BoP). The adopted research strategy is a case study of a multinational subsidiary whose unit of analysis is the development of a frugal product from its inception to its presence in the market. A theoretical model that identifies the antecedents, processes, and results of frugal innovation supports data analysis. This study thus contributes establishing propositions that give specificity to the model with regard to the expansion of multinationals in an emerging market. The results reveal that strategy and brand consolidation precede the development of a frugal product, which is followed by systematic analysis of market characteristics, consumer behavior, and local competition. Additionally noteworthy are the horizontal integration and dynamic interaction of marketing and production; the adoption of a design that integrates basic functionalities, qualities, aesthetic attributes; and the minimal use of resources, the elimination of nonessential functionalities, the adoption of modularity as a production strategy, and the mastery of skills in production and learning strategies. Finally, the findings indicate the relevant combination and dynamization of organizational capabilities and their influence in reversing the technology transfer orientation between headquarters, as well as the consequences of frugal innovation.